Oh Canadiana? Atlantic Canada, Joel Thomas Hynes, and Heroin Realism - Polley, Jason S. (Studia Anglica Posnaniensia, 2020)
The essay locates Joel Thomas Hynes’s We’ll All Be Burnt in Our Beds Some Night (2017), narrated by the social outcaste Johnny, in an international “heroin realism” tradition. Hynes, styled as Canada’s “bad boy” author, thus evoking his emotional ties to his protagonist, situates Johnny on the margins of Canada: in Newfoundland, which has been systemically disenfranchised from Canada’s centre beside the rest of Atlantic Canada for over a century, as novels by Michael Crummey, Lisa Moore, David Adams Richards, Alistair MacLeod, and Hugh MacLennan show. The regionally representative Johnny complicates romantic figurations of Canada, which prides itself on progressiveness and equal opportunity, and which is globally envisaged as a beacon of mobility and community. Characters like Johnny do not fit into mythical Canada, whether in its pan-Canadian variety, where the East Coast is mythologized as an ocean oasis of what Herb Wyile calls “commercial antimodernism,” or in its depressive, alcoholic Atlantic-Canadian version. Limited by his social positioning, ot unlike Rose in Alice Munro’s collection The Beggar Maid (1978), Johnny cannot actualise the mobility Canadiana advertises – this despite his inculcation of this seductive delusion via books. He instead experiences what bell hooks calls “psychic turmoil”: the discomfiture of simultaneously occupying two distinct yet continuous narratives. Johnny’s regional narrative, then, not only translates to Rose’s national one, as well as to the spirit of the Beats, of road novelists, and of Hunter S. Thompson’s gonzo, but also to the international dimensions of other personages in “heroin realism.” Writers like Joel Thomas Hynes, Harry Crews, Denis Johnson, Antonio Lobo Antunes, Jeet Thayil, Eimear McBride, and Niall Griffiths work to deconstruct romantic idealizations. The figures of heroin realism, like Johnny, are those characters who are neither commoditized by class relations nor by national narratives.